The Effect of Education on the Utilization of Posyandu During the Covid 19 Pandemic in Sei Rattan Village, Percut Sei Tuan District, Deli Serdang Regency - Yetti Fauziah Silalahi (Journal of Midwifery and Nursing, 2022)
Posyandu is a form of health service where the management and implementation come from, by and with the community to improve health development, improve public health by empowering the community, and become a basic service for the community in order to accelerate the reduction of maternal and infant mortality. This type of research is a pre-experiment using a one group pretest posttest design. The population in this study were mothers who attended the posyandu, totaling 35 people using the Sampling Technique: Purposive Sampling. The purpose of this study was to determine whether there was an effect of providing education on the use of posyandu during the covid 19 pandemic. The results of the research on the use of posyandu during the Covid 19 pandemic before providing education, the majority were still low at 18 respondents (46.2%), while the use of posyandu during the Covid 19 pandemic after providing education increased to a high category of 20 respondents (51.3 %). Conclusion There are differences in the quality of posyandu utilization during the Covid 19 pandemic before and after being given education, with a p value (0.000) < (0.05). These results prove that there is a significant effect between the provision of education on the use of Posyandu during the COVID-19 pandemic in Sei Rotan Village. These results prove that the provision of education can provide positive changes to the use of Posyandu during the covid pandemic.